Comparative assessment of erythrocyte sphingolipid levels as potential cardiovascular health markers in women from Libya and Serbia: a small-scale study - Nevena Vidović; Marija Knez; Marija Ranić; Fathia Faid; Dragana Jović; Marija Glibetic; Marija Takić (Libyan Journal of Medicine, 2023)
ABSTRACTAim: Cardiovascular diseases (CVDs) represent the major cause of morbidity and mortality worldwide including Libya, where they account for 43% of all deaths. Sphingolipids are involved in the pathology of numerous diseases including cardiovascular diseases and are proposed as potential biomarkers of cardiovascular health that could be more effective compared to traditional clinical biomarkers. The aim of this study was to determine the sphingolipid content in the erythrocyte membrane of Libyan migrant and Serbian resident women. In addition, to examine if sphingolipid levels could be used as a novel indicator of cardiovascular risk, we evaluated possible correlations with some well-established biomarkers of cardiovascular health.Materials and Methods: A total of 13 Libyan and 15 Serbian healthy women participated in the study. The high-performance version thin-layer chromatography (HPTLC) using the image analysis tool JustTLC was applied for quantification of erythrocytes’ sphingolipids.Results: Lower mean values of erythrocytes’ sphingolipids and cholesterol concentrations were found in the group of Libyan emigrants compared to Serbian resident women. Besides, in this group of apparently healthy women (n = 28), the sphingolipid content of erythrocytes was inversely related to the Omega-3 index (r =-0.492, p = 0.008) and directly linked to vitamin D status (r = 0.433, p = 0.021) and membrane cholesterol levels (r = 0.474, p = 0.011).Conclusion: The erythrocytes’ sphingolipid levels should be measured/assessed as an additional biomarker of CV health, by applying a simple and routine method. Still, further investigation in a larger population-specific context is warranted.